Implementation of TikTok as Medium for Learning of English Vocabulary: The Perspective of Department English Education Students - Elsa Dwipa; Raden Ajeng Nafiah Khoirunisa; Fajar Gibran Al-Haqq; Aghna Thurfah Aqilah; Reza Anis Maulidya (Universitas Cokroaminoto Palopo, 2024)
This research aims to examine students' perspectives on implementing the TikTok application as a medium for learning English in the modern era. Especially with the latest technological advances, in the post-pandemic COVID-19 social media can be used as a learning media such as YouTube, Twitter, Instagram, Facebook, and TikTok applications. TikTok can help students improve their English language proficiency, as well as what problems and difficulties arise when using the application as a vocabulary teaching tool and what difficulties students may encounter when using TikTok to learn new vocabulary. This research uses a qualitative design with a survey method where students fill out an online questionnaire using Google Forms and interviews. Questionnaires were given to students, and then students were interviewed. The participants were 30 students who took part in the English language learning program. The research results show that the students had a positive response to the use of TikTok in learning English vocabulary. TikTok ease of use and various functions, the TikTok application can be applied to learning activities to increase English vocabulary. This interactive learning media can provide much educational content about English vocabulary and make the learning process more efficient and effective for students. The implementation of This research makes it possible for educators. Content creator educators can easily create a learning process that attracts students' attention. It has been known that the TikTok application is efficient in increasing English vocabulary for students. Through the TikTok application, students can gain more vocabulary and continue to have fun learning by presenting information through interesting content, audio and visuals. Teachers can also process and develop various sources of interactive, interesting and unique TikTok content. So that it makes students interested in learning English and considers TikTok to be an effective medium for learning.